1992
DOI: 10.1002/jab.770030208
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive ceramics for periodontal treatment: Comparative studies in the patus monkey

Abstract: Four bioactive ceramic materials currently recommended for regeneration of osseous tissues in treatment of periodontal disease have been compared with Bioglass particulates, of equivalent size in two compositions, in a monkey model. Both Bioglass materials were found to be easily manipulated, were haemostatic and osteoproductive allowing restoration of both alveolar bone and periodontal ligament. Epithelial downgrowth was inhibited and epithelial attachment was close to the preimplantation level. The other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
168
0
7

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(176 citation statements)
references
References 8 publications
1
168
0
7
Order By: Relevance
“…15 At this instance, the regenerative healing of periodontal lesions after application of bioactive glass was histologically examined in animals by Wilson and Low, Karatzas et al reported the new cementum formation with collagen fiber insertion, and no long junctional epithelium at the bioactive glass site. 16,17 In contrary to the above studies, Nevins ML, et al evaluated Bioglass histologically in five human periodontal defects, and confirmed the new formation of root cementum and connective tissue attachment at only one tooth. 18 There are currently limited studies available comparing the treatment outcomes of bioactive glass in the treatment of intrabony defects in aggressive periodontitis.…”
Section: Karatzas S Zavrasmentioning
confidence: 94%
“…15 At this instance, the regenerative healing of periodontal lesions after application of bioactive glass was histologically examined in animals by Wilson and Low, Karatzas et al reported the new cementum formation with collagen fiber insertion, and no long junctional epithelium at the bioactive glass site. 16,17 In contrary to the above studies, Nevins ML, et al evaluated Bioglass histologically in five human periodontal defects, and confirmed the new formation of root cementum and connective tissue attachment at only one tooth. 18 There are currently limited studies available comparing the treatment outcomes of bioactive glass in the treatment of intrabony defects in aggressive periodontitis.…”
Section: Karatzas S Zavrasmentioning
confidence: 94%
“…Slow release of soluble ions from the material stimulates cell division and production of growth factors and ECM proteins. Mineralization of the matrix follows and the mature osteoblast phenotype, encased in a collagen -HCA matrix (osteocytes), is the final product both in vitro and in vivo (Wilson & Low 1992;Hench et al 2000;Xynos et al 2000aXynos et al ,b, 2001Bielby et al 2004Bielby et al , 2005Gough et al 2004;Christodoulou et al 2005a,b).…”
Section: Third-generation Biomaterials: Cell-and Gene-activating Matementioning
confidence: 99%
“…Materials Science and Engineering C 33 (2013) [2757][2758][2759][2760][2761][2762][2763][2764][2765] As an alternative, bioactive glasses are being used as a bone healing strategy [10][11][12]. The currently FDA approved glass for these applications is known as Perioglass™ (Mo-Sci, Rolla, MO) and is based on the chemistry of Hench's Bioglass™ (45S5, 45 wt.% SiO 2 , 24.5 wt.% Na 2 O, 24.5 wt.% CaO, 6 wt.% P 2 O 5 ).…”
Section: Introductionmentioning
confidence: 99%